Improving communication, problem-solving, and self-efficacy skills grade-10 students through scientific approach based on discovery learning - Rahmi, Cut Nadia; Jailani, Jailani; Chrisdiyanto, Endar (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2024)
Education plays an important role in creating a young generation to be able to compete in the era of globalization, one of which is through mathematics learning. The objectives of mathematics learning include mathematical communication, learning to reason mathematically, learning to solve problems, and learning to connect ideas. These abilities are abilities that students must have in facing global challenges. This study aims to determine the improvement of communication skills, the sharpness of mathematical problem solving, and self-efficacy using a scientific approach through the application of the discovery learning model. This study is a quantitative study, and the type of research used in this study is quasi-experimental. The research design used is one group pretest-posttest. This study was conducted in one of the high schools in West Aceh. The study population was 29 grade 10 students. Data collection techniques used test and non-test methods. The findings of the study showed a significant increase in communication skills, problem-solving abilities, and self-efficacy when using the discovery learning approach in the context of trigonometric ratios. The approach is considered quite effective, which means it produces a substantial increase in the cognitive abilities mentioned above among students.